Physicalism and privacy - Altmann, D; Daniel Altmann (1978)
﻿ The main objective of this thesis is to indicate an approach through which ontological dualism of mind and body may be collapsed - to show that (and how) the intuitive resistance to ontological monism is confused. A minor objective, much less extensively argued for, is to indicate that once we can accept that there is no logical obstacle to the view that we are purely physical, then human mentality poses no logical obstacle to the scientific accommodation of human beings - to physicalism. It is argued that we already have, in Wittgenstein's Private Language Argument, a very powerful argument suggesting that ontological dualism is logically unsound. The assessment of Wittgenstein's impact on ontological dualism occupies the first major section of the thesis (Part 2). But it is found that the logical force of Wittgenstein's argument, though successfully applicable against ontological dualism, does not prescribe the sort of monistic account we should adopt. For there are two alternatives which satisfy Wittgenstein's argument, which is essentially an argument banishing necessarily "private" mental events. One alternative involves abandoning the view that we can be introspectively aware of mental events (essentially a behaviourist approach). The other alternative is to retain the possibility of introspective awareness of mental events, while maintaining that the latter are only contingently "private" (an approach with which the mind-brain identity theory may be aligned). The first alternative is summarily rejected as being too counter-intuitive; and the remainder of the thesis explores the viability of the second alternative. But the latter alternative is also counter-intuitive: the dualist and the unconvinced materialist resist the suggestion that the mental events of which we may be introspectively aware could be neural events occurring in the brain or central nervous system. In Part 5 the mind-brain identity theory is discussed. The strategy underlying this approach, as generally conceived, is found not only to be unstable and ambivalent - straddling two rather different views - but also to be marked by a reluctance to engage sympathetically with the dualist's resistance. In Part 4 an attempt is made to examine and undermine this resistance. It is found that this resistance is set in a context involving a confused form of realism; and the confusion is traced to a familiarly mistaken notion of perception, in which mental perceptual events are taken to mediate between a "mental subject" and the "external world". The attempt to expose the confusions involved here, and to present a more satisfactory realism in a monistic setting, is supported by a formallinguistic treatment of the relevant aspects of perception. In this formal account, which requires some elementary set-theoretical notions (in particular the notion of isomorphism), a designatory role is defined for perceptual events taken as syntactic entities in a certain sort of formal language. Through this formal treatment it is shown that for a rich enough (purely) physical structure there would be a "subjective dualism": essentially a symptom of the fact that for a physical structure to "perceive" a physical event, there would have to occur in it an unperceived (physical) event. And it is suggested that the dualist's resistance is based on a confusion in which what he takes to be a justification for ontological dualism can only be taken as a justification for "subjective dualism". As a result of these considerations a modified form of the mind-brain identity theory is advocated, in which mental events for whose occurrence we can have introspective evidence are construed as unperceived (but not imperceptible) physical events which (it is hypothesised in the case of human beings) have neurophysiological descriptions. In Part 5 this view is considered in a more general context. Also in this section there is an argument for a view hinted at earlier in the thesis, maintaining that the peculiarities of "mental discourse" pose no serious problem for physicalism. Finally, two problems connected with the notions of the "unity" and "simplicity" of mind are briefly mentioned, and an indication is given as to how they may be handled by the present account.